THE NEW APPROACHES TO THE CONCEPT OF TRANSLATION THEORY AND PRACTICE. (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
This abstract is designed for university students as well as intelligent explorers.This article about the educational value of translational theory. In this abstract is expressed about approaches to the translation theory in our modern society,the role of the internship during the our lifestyle and for our career.In addition  about the formation of the skills the processing practice.Most importantly it discusess the concept of translational theory and theoretical basis of the article evaluation and methodology.